2022
DOI: 10.1039/d1ee03311e
|View full text |Cite
|
Sign up to set email alerts
|

Sublayer-enhanced atomic sites of single atom catalysts through in situ atomization of metal oxide nanoparticles

Abstract: The in situ atomization of carbon supported metal oxide nanoparticles provides a novel strategy to synthesize atomic sites supported on highly graphitized carbon materials with high metal loading and controlled atomic layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…This supplies a facile and practical route for efficient PGM-free catalysts for HT-PEMFCs. The Cheng group most recently demonstrated that the in situ growth of atomic layers of iron single atoms on carbon supports could boost the turnover frequency by using the sublayer to tune the activity of the top-layer atomic sites, enhancing the activity and durability for the ORR [237]. Interestingly, tuning the CO content (0-10%) within the hydrogen stream has also been reported to actually possibly reduce the carbon corrosion rate occurring during start-stop [238], while carbon corrosion can also be mitigated through careful control of HT-PEMFC operation [239].…”
Section: Pgm-free Catalysts For Ht-pemfcsmentioning
confidence: 99%
“…This supplies a facile and practical route for efficient PGM-free catalysts for HT-PEMFCs. The Cheng group most recently demonstrated that the in situ growth of atomic layers of iron single atoms on carbon supports could boost the turnover frequency by using the sublayer to tune the activity of the top-layer atomic sites, enhancing the activity and durability for the ORR [237]. Interestingly, tuning the CO content (0-10%) within the hydrogen stream has also been reported to actually possibly reduce the carbon corrosion rate occurring during start-stop [238], while carbon corrosion can also be mitigated through careful control of HT-PEMFC operation [239].…”
Section: Pgm-free Catalysts For Ht-pemfcsmentioning
confidence: 99%
“…Due to the existence of new characteristics such as unsaturated coordination environment, high surface free energy, and local electronic structure adjustment of single atoms, [20][21][22] they exhibit excellent selectivity, activity, durability, and other catalytic performances for various catalytic reactions. Of course, an efficient coordination environment is inseparable from the induction of carriers, such as metal oxides, [23][24][25] graphene, 26,27 hexagonal boron nitride (h-BN), 28,29 covalent organic frameworks (COFs), 30 metal-organic polyhedra (MOP), 31 and metal-organic frameworks (MOFs), which is essential for the local environmental regulation of metal single atoms (Me-SAs) in SACs. Besides, the successful synthesis of SACs also signicantly reduces the cost of preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen coordination transition metal single atom catalysts supported on carbon matrix (SACs‐NC) feature the maximum atomic utilization and unique electronic structure, [ 1 , 2 , 3 ] and show great potential in fields of energy conversion and chemical synthesis. [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ] In order to achieve its promising application, splendid efforts had been made in developing synthetic strategy for well‐defined SACs‐NC, especially the strategy for large‐scale preparation, but still challenging. [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ] Of the various pioneering innovations, the strategy combining metal ion impregnation and annealing (MIA) is considered as the approach that most commonly used and most amenable to scale‐up due to its easy operation and low cost.…”
Section: Introductionmentioning
confidence: 99%